Development of Mathematics E-Modules with Cultural Context to Support Mathematical Literacy - A'yun, Rhoro Qurota; Anwar, Lathiful; Kusumasari, Vita (Universitas Islam Lamongan, 2025)
This research aims to develop a culture-based mathematics E-Module to support students' mathematical literacy in a valid, practical, and effective way. The ADDIE development model was used in this research. Data was collected with validation sheets, response questionnaires, and evaluation questions and analyzed descriptively qualitative and quantitative. The validity of the E-Module, with a validation score of 81.5%, fits the valid criteria. Practicality with a response questionnaire score of 90.49% according to practical criteria. Effectiveness was assessed from student evaluation results with an average percentage of 63.166% according to somewhat effective criteria. The results showed that the E-Module with cultural context is feasible and practical and has a positive impact on improving students' mathematical literacy skills.